Examining the impact of surface material design treatments on traditional and collaborative instructional approaches in hybrid classrooms - Abdul Wafi, Razali; Nazli, Che Din; Musli Nizam, Yahya; Raha, Sulaiman; Asrul Sani, Abdul Razak (2025)
Hybrid teaching has gained substantial interest in higher education and is anticipated to influence future pedagogical reforms worldwide in the aftermath of the pandemic. Despite the adaptability of hybrid teaching as a flexible instructional design, various limits have emerged. Poor sound quality was a major challenge for distant students, impairing their ability to effectively comprehend lectures and engage in interactions with on-site peers and instructors. Therefore, this study aims to investigate the impact of surface material design treatment on two distinct educational approaches in hybrid classroom environments, namely lecture-based and collaborative learning. This study incorporates field measurements and acoustic modelling methods to develop effective surface design treatments that enhance the listening experience for remote students. Three significant acoustic parameters were assessed: reverberation time (RT), speech transmission index (STI), and speech clarity (C50). The results indicate that surface treatment on wall and ceiling areas have a substantial impact on the important acoustic parameters that emphasizes on speech intelligibility. The findings from an in-depth investigation are beneficial for designers and educational institutions in ensuring appropriate acoustic quality for hybrid learning settings. This setting concurrently enhances students' learning experiences and performance.